Integration and learning: a case study of the international higher physical education talent-cultivation model - Song, Bruce; Xi, Jun; Li, Shichen; Zhou, Yuan; Zhang, Qiangfeng; Zhou, Huixuan; Feng, Chen; Grecic, David; Peng, Xiyang (Frontiers in Education, 2024)
Introduction This study delves into the multifaceted components of talent-training models within China’s physical education domain through Sino-foreign cooperative initiatives. Employing a mixed-methods approach, it systematically evaluates the innovative systems developed by pilot units and outlines their experiential insights. Methods Using a mixed-methods approach, this research extensively evaluates the situation of pilot units by collecting and analyzing data from closed-ended and open-ended questionnaires as well as interview responses. The study categorizes and analyzes the data to comprehensively understand cooperative talent-training models. Results The findings are classified into three main themes: Learning, Integration, and Binary Evaluation and Practice Reform. Under the Learning theme, the study observed a selective integration of foreign educational paradigms into the local context, respecting the distinctiveness of Chinese education and aligning with national policies promoting unique educational systems. Additionally, the Integration theme underscores the necessity of meticulously assimilating introduced educational resources into China’s educational fabric, highlighting the need for adaptability when integrating foreign educational elements. Furthermore, the Binary Evaluation and Practice Reform theme reveal the establishment of a dualistic evaluation and reform system tailored to cooperative education specifics, outlining challenges associated with ideological and cultural disparities when integrating certain foreign education aspects into the Chinese context. Discussion This research provides insightful exploration into the complexities of collaborative talent-training models in Physical Education. It not only elucidates the assimilation of foreign paradigms but also highlights nuanced challenges and prospects for developing tailored educational systems within specific regional and national contexts.